PERILAKU INOVATIF PENGAWAS SEKOLAH DALAM SUPERVISI AKADEMIK PADA SMA DI KABUPATEN DELI SERDANG - Khairuddin Khairuddin (Jurnal Guru Kita PGSD, 2019)
Abstract:Innovative Behavior of School Supervisors in Academic Supervision in Senior High Schools in Deli Serdang Regency. In this study, the researchers analyzed the relationship of innovative behavior of school supervisors in the assessment of school principals and senior high school teachers in Deli Serdang regency. The results of this study indicate the diversity of data acquisition results using the Likert method almost towards strongly agreeing with the dimensions given to principals and high school teachers with a R2 value of 0.55 (55%). Statistical regression results show a close relationship between the average value of the teacher and the principal. The lowest value obtained from this study is in the location of Pancur Batu, this must be improved in the treatment of academic supervision in high schools in Deli Serdang district with a value of 3.97 (Pancur Batu People's Private High School) and 4.01 (Pancur Batu Methodist Private High School).Keywords: Innovative Behavior, School Supervisor, Teacher, LikertAbstrak: Perilaku Inovatif Pengawas Sekolah dalam Supervisi Akademik pada SMA di Kabupaten Deli Serdang. Dalam penelitian ini, peneliti melakukan analisa hubungan perilaku inovatif pengawas sekolah dalam penilaian kepala sekolah dan guru sekolah menegah atas (SMA) di kabupaten Deli Serdang. Hasil penelitian ini menunjukkan keberagaman hasil perolehan data menggunakan metode likert hampir menuju sangat setuju dengan dimensi yang diberikan kepada kepala sekolah dan guru SMA dengan nilai R2 yaitu 0,55 (55%). Hasil regresi statistik menunjukkan hubungan yang erat antara nilai rata-rata guru dan kepala sekolah. Nilai terendah yang diperoleh dari penelitian ini berada di lokasi Pancur Batu, hal ini harus ditingkatkan dalam perlakuan supervisi akademik pada SMA di kabupaten Deli Serdang dengan nilai 3,97 (SMAS Rakyat Pancur Batu) dan 4,01 (SMAS Methodist Pancur Batu). Kata Kunci :Perilaku inovatif, Pengawas sekolah, Guru, Likert